ACPTDF for Multi-transactions and ATC Determination in Deregulated Markets - Ashwani Kumar Sharma; Jitendra Kumar (International Journal of Electrical and Computer Engineering (IJECE), 2011)
Abstract—Available transfer capability in the transmission network has become essential quantity to be declared well in advance for its commercial use in a competitive electricity market. Its fast computation using DC load flow based approach is used worldwide for on line implementation. Many authors have proposed the ATC calculation based on DC/AC load flow approach. In this paper, AC PTDF based approach has been proposed for multi-transaction cases using power transfer sensitivity and Jacobian calculated with three different methods. The methods can be implemented for any number of transactions occurring simultaneously. The results have been determined for intact and line contingency cases taking multi-transaction/simultaneous as well as single transaction cases. The main contributions of the paper are: (i) ATC determination for multi-transactions environment, (ii) ATC determination and comparison with three approaches of PTDF calculations, (iii) LODFs with line contingency cases for multi-transaction environment and thereby ATC determination. The results have also been obtained with DC method for comparison. The proposed method have been applied for IEEE 24 bus RTS. Keywords: Available transfer capability, AC load flow, AC power transfer distribution factors , line outage contingency, line outage distribution factors, multi-transactions, simultaneous transactions.DOI:http://dx.doi.org/10.11591/ijece.v1i1.61